Controllability conditions for chemical and microbiological systems. (September 2022) - Virágh, Eszter; Dochain, Denis
Abstract: To solve (bio)chemical problems, often required to control the processes. However, the investigated system is not controllable at every state–space point. It is necessary to know what conditions must be provided for controllability. In this paper, we determine conditions for the controllability of chemical and microbiological reactions in isothermal and non-isothermal cases. In two examples, we show how can be applied the results in the study of different processes. Highlights: Controllability conditions can be specified for special form systems. The controllability conditions depend on the type of the reactor. The controllability is influenced by the temperature dependence of the process.